Nutrition Labeling - Mulamari, Hemasree (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
This paper aims to highlight the importance of nutrition labeling. This FDA propose technique helps the consumers to make good nutrition choices. Application of Nutrition labeling is a must Therefore, the suggested model is particularly useful to understand the domain specific label utilization and its utmost importance. The paper highlights the importance of nutrition labeling in the food marked along with is negative effects.